Framing disaster resilience: The implications of the diverse conceptualisations of "bouncing back". Issue 3 (27th May 2014) - Aldunce, Paulina; Beilin, Ruth; Handmer, John; Howden, Mark
Abstract : Purpose: – To confront the increasingly devastating impacts of disasters and the challenges that climate change is posing to disaster risk management (DRM) there is an imperative to further develop DRM. The resilience approach is emerging as one way to do this, and in the last decade has been strongly introduced into the policy arena, although it is not new for DRM practitioners and researchers. Nevertheless, resilience is a highly contested issue, and there is no agreed definition of it, which has resulted in confusion for stakeholders when applying it to practice. Therefore, the purpose of this paper is to investigate how resilience is framed by researchers and DRM practitioners. Design/methodology/approach: – The analytical framework used was Hajer's "social-interactive discourse theory", combined with analysis of government documents, in-depth interviews with practitioners and observation of field and practices within the context of the Natural Disaster Resilience Program in Queensland, Australia. Findings: – One of the key findings is that the idea of "bouncing back" is central to the resilience discourse but different interpretations of this idea results in real-world implications. Three different ways (storylines) in which practitioners construct the meaning of disaster resilience emerge from this study. Importantly the divergences between these storylines reveal possibilities for reframing to occur and these could lead to different policy options and practices. Originality/value: – The results presented in this paper offer empirical evidence on how resilience is understood on the ground, contributing to extending resilience theory and informing DRM and resilience practice.